First report of coexistence of blaKPC-2 and blaNDM-1 in carbapenem-resistant clinical isolates of Klebsiella aerogenes in Brazil - Rodrigues, Saulo Henrique; Nunes, Gustavo Dantas; Soares, Gabriela Guerrera; Ferreira, Roumayne Lopes; Damas, Marcelo Silva Folhas; Laprega, Pedro Mendes; Shilling, Rebecca Elizabeth; Campos, Leslie Camelo; da Costa, Andrea Soares; Malavazi, Iran; da Cunha, Anderson Ferreira; Pranchevicius, Maria-Cristina da Silva (Frontiers in Microbiology, 2024)
Klebsiella aerogenes is an important opportunistic pathogen with the potential to develop resistance against last-line antibiotics, such as carbapenems, limiting the treatment options. Here, we investigated the antibiotic resistance profiles of ten K. aerogenes strains isolated from patient samples in the intensive-care unit of a Brazilian tertiary hospital. All isolates were completely resistant to β-lactam antibiotics, including ertapenem, imipenem, and meropenem with differencing levels of resistance to aminoglycosides, quinolones, and tigecycline also observed. Half of the strains studied were classified as multidrug-resistant. The carbapenemase-producing isolates carried many genes of interest including: β-lactams (blaNDM-1, blaKPC-2, blaTEM-1, blaCTX-M-1 group, blaOXA-1 group and blaSHVvariants in 20-80% of the strains), aminoglycoside resistance genes (aac(6')-Ib and aph(3′)-VI, 70% and 80%), a fluoroquinolone resistance gene (qnrS, 80%), a sulfonamide resistance gene (sul-2, 80%) and a multidrug efflux system transporter (mdtK, 70%) while all strains carried the efflux pumps Acr (subunit A) and tolC. Moreover, we performed a comprehensive genomic characterization of a specific K. aerogenes strain (CRK317) carrying both the blaKPC-2 and blaNDM-1 genes simultaneously. The draft genome assembly of the CRK317 had a total length of 5,462,831 bp and a GC content of 54.8%. The chromosome was found to contain many essential genes.In silico analysis identified many genes associated with resistance phenotypes, including β-lactamases (blaOXA-9, blaTEM-1, blaNDM-1, blaCTX-M-15, blaAmpC-1, blaAmpC-2), the bleomycin resistance gene (bleMBL), an erythromycin resistance methylase (ermC), aminoglycoside-modifying enzymes (aac(6')-Ib, aadA/ant(3'')-Ia, aph(3')-VI), a sulfonamide resistance enzyme (sul-2), a chloramphenicol acetyltransferase (catA-like), a plasmid-mediated quinolone resistance protein (qnrS1), a glutathione transferase (fosA), PEtN transferases (eptA, eptB) and a glycosyltransferase (arnT). We also detected 22 genomic islands, eight families of insertion sequences, two putative integrative and conjugative elements with a type IV secretion system, and eight prophage regions. This suggests the significant involvement of these genetic structures in the dissemination of antibiotic resistance. The results of our study show that the emergence of carbapenemase-producing K. aerogenes, co-harboring blaKPC-2 and blaNDM-1, is a worrying phenomenon which highlights the importance of developing strategies to detect, prevent, and control the spread of these microorganisms.